The regulatory role of aberrant methylation of microRNA-34a promoter CpGs in osteosarcoma - Shi, Jiandang; Zhao, Chen; Liu, Xuejiao; Zhang, Bing; Wang, Peng; Yang, Zongqiang; Niu, Ningkui (Translational Cancer Research; Vol 8, No 6 (October 30, 2019): Translational Cancer Research, 2019)
Background: The methylation of microRNAs (miRNAs) and DNA play an important role in the development of tumors. MiRNA-34a can inhibit the proliferation and metastasis of osteosarcoma cells. It was approved in a variety of tumors studies that abnormal promoter methylation leads to the reduction of miRNA-34a expression. This study investigated the regulation and mechanisms of miRNA-34a and promoter 5'-C-phosphate-G-3' (CpG) methylation in osteosarcoma cells. Methods: To identify whether the abnormal methylation of miRNA-34a promoter occurs in osteosarcoma cells, and the relationship between abnormal methylation and miRNA-34a expression, we used matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) to compare differences in the methylation of miRNA-34a promoter CpGs between osteosarcoma cells and osteoblasts, and osteosarcoma tissues and normal bone tissues, respectively. The quantitative polymerase chain reaction (qPCR) was used to compare the difference in the expression of miRNA-34a. The human osteosarcoma cells were demethylated and the miRNA-34a expression was upregulated to detect changes in the methylation of miRNA-34a promoter CpGs and the level of miRNA-34a expression. The regulation and mechanism of miRNA-34a and its promoter CpGs was analyzed. Results: We found abnormal hypermethylation in miRNA-34a promoters CpG1, CpG3, CpG5, and CpG7, and significant decrease in miRNA-34a expression. In osteosarcoma cells, miRNA-34a expression was increased following decreased methylation of miRNA-34a promoter CpG5, and the proliferation rate of osteosarcoma cells was decreased, indicating that hypermethylation of promoter CpG5 might negatively regulate miRNA-34a expression. After the expression of upregulated miRNA-34a, the expression of DNA (cytosine-5)-methyltransferase 1 (DMNT1) in osteosarcoma cells and the methylation level of miRNA-34a promoter CpG5 were both decreased, showing that miRNA-34a could negatively regulate the methylation of promoter CpG5 by DNMT1. Conclusions: In osteosarcoma cells, abnormal hypermethylation occurred in some miRNA-34a promoter CpGs. MiRNA-34a and its promotor methylation negatively regulated with each other. Among the promoters, CpG5 has a significant specificity and is expected to be the target of diagnosis and treatment for osteosarcoma.